Rights-Based School Governance in Indonesia: Reconstructing Educational Management for Student Protection Under the 2026 Safe and Comfortable School Culture Framework - Heri Kiswanto; Deni Irawan (Adagium: Jurnal Ilmiah Hukum, 2026)
This article examines how educational management can be reconstructed as a governance mechanism for fulfilling and protecting students' rights within Indonesian education law, particularly following the 2026 regulatory shift toward a Safe and Comfortable School Culture. Using normative legal research, the study combines statutory and conceptual approaches. Primary legal materials include constitutional guarantees, education, child-protection, disability and personal-data legislation, as well as the latest school-management and safe-school regulations. Secondary materials comprise recent Indonesian and international peer-reviewed scholarship on education rights, inclusion, student voice, school leadership, safety and institutional accountability. The analysis finds that students' rights extend beyond formal access to schooling and encompass continuity of learning, substantive equality, physical and psychological safety, sociocultural and digital security, reasonable accommodation, meaningful participation, accessible complaints and effective remedy. The article develops a Rights-Based School Governance (RBSG) model with six interdependent dimensions: legal alignment and rights mapping; inclusive planning and equitable resource allocation; a safe and dignified learning environment; meaningful student participation; accessible complaint, response and remedy; and rights-based monitoring, evaluation and accountability. The model translates abstract legal duties into auditable managerial processes while preserving professional authority and institutional proportionality.